A New Model for the Evolution of Oceanic Transform Faults Based on 3D Broadband Seismic Observations From São Tomé and Príncipe in the Eastern Gulf of Guinea - Myron F. H. Thomas; Christian Heine; Jimmy vanItterbeeck; Ilya Ostanin; Andrey Seregin; Michael Spaak; Tamara Morales; Tess Oude Essink (Geochemistry, Geophysics, Geosystems, 2022)
Abstract Oceanic Transform Faults are one of manifestations of the three major plate boundaries and a key tectonic feature of oceanic crust. They are broadly considered to accommodate strike‐slip displacement along simple vertical faults and to be largely without magmatic addition. We present the first observations from broadband 3D seismic of buried, Cretaceous‐aged transform faults in the Gulf of Guinea with complex internal architectures including crustal scale detachments and rotated packages of volcanics within oceanic crust. In the study area, several Oceanic Fracture Zones (OFZ) are described from Top Crust to Moho. OFZ scarps are observed to connect at depth with zones of low angle reflectivity which dip into the OFZ and perpendicular to the spreading orientation. At depth they detach onto the Moho, necking the adjacent crust in the manner of extensional shear zones. Thickly stacked and tilted reflectors, interpreted as extrusive lava flows, are common above the shear zones and infill up to 75% of the crustal thickness. The entire OFZ stratigraphy is overlain and sealed by late‐stage lavas that are continuous from the abyssal hills of the trailing spreading ridge. These insights demonstrate complexity previously only predicted in numerical simulations. We propose a model with extension at a high angle to the spreading orientation along a low angle shear zone that acts as a conduit for decompression related melt and volcanism. We conclude that oceanic transforms are non‐conservative and not simple strike slip fault zones, contradicting the conventional view.